Kalimantan Region Economic Growth and Poverty as Analyzed by Capital Expenditures, Human Development Index, and Inflation - Br Sirait, Pebri Hidayanti (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2023)
This study aims to analyze the effect of Capital Expenditure, Human Development Index and Inflation on Economic Growth and Poverty in the Kalimantan Region. The data used in this study is a type of secondary data. These data are obtained from the Central Bureau of Statistics (BPS) publications. The method used in this research is Path Analysis. The results of this study indicate that capital expenditure has a direct and insignificant positive effect on economic growth, the human development index has an immediate and significant positive impact on economic growth, inflation has a direct and consequential positive effect on economic growth, capital expenditure has a direct and indirect negative effect. Important to poverty, the human development index has an immediate and significant adverse impact on poverty, inflation has a direct and insignificant positive effect on poverty, and economic growth shows a direct and consequential positive impact on poverty